Being Tired or Having Much Left Undone: The Relationship Between Fatigue and Unfinished Tasks With Affective Rumination and Vitality in Beginning Teachers - Weiher, Gerald M.; Varol, Yasemin Z.; Horz, Holger (Frontiers in Psychology, 2022)
The present diary study was conducted for the purpose of bridging and integrating empirical research on the antecedents and consequences of work-related ruminative processes in the evening. Based on the control theory, unfinished tasks and fatigue in the afternoon were considered as antecedents of affective rumination, while vitality was investigated as the outcome observed in the next morning to test for cyclical processes. During a five-day diary study (including three weekdays and the weekend), 74 beginning teachers completed three diary entries per day. A total of 792 diary entries were obtained. Using multilevel structural equation modeling, the study supported that both fatigue and unfinished tasks explained unique shares of variance of affective rumination in the evening at the between- and within-person levels. Furthermore, affective rumination mediated the relationship between unfinished tasks and vitality as well as fatigue and vitality. However, this only held true at the between- and not the within-person level, as neither affective rumination nor fatigue and unfinished tasks predicted the following morning’s vitality at this level. The results offer insights into the antecedents of affective rumination and add to extant research on the negative consequences of affective rumination considering vitality as an outcome.